Radioactivity in the Marine Environment: Understanding the Basics of Radioecology. Issue 1 (27th December 2018) - Benitez‐Nelson, Claudia R.; Charmasson, Sabine; Buesseler, Ken; Dai, Minhan; Aoyama, Michio; Casacuberta, Núria; Godoy, José Marcus; Johnson, Andy; Maderich, Vladimir; Masqué, Pere; Metian, Marc; Moore, Willard; et al.
Abstract : Natural and anthropogenic radionuclides are ubiquitous in the marine biosphere. They are used to study a suite of environmental processes, including those related to marine food webs, yet they also potentially negatively impact marine biota and humans. The goal of this lecture is to provide upper level undergraduate and graduate students with a basic understanding of marine radioecology and how marine organisms bioaccumulate and influence the cycling of radionuclides in the environment. The lecture begins with a brief introduction to the methods and models used to understand biological radionuclide uptake and loss, followed by how organisms biogeochemically and physically transfer radioactive substances throughout the ocean. The remaining lecture focuses on current methods for assessing potential radiological impacts on marine biota and risks associated with contaminated seafood consumption. This is the last lecture of a four‐part lecture series on radionuclides in the marine environment.